(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The role of girls entrepreneurs has changed over the years in the world. Participation and their importance are commendable in the country’s economic growth and development. the planet Development Report, 2021represents that ladies owned businesses show great potential source of future for economic growth and job creation. Therefore, many initiatives are started by United Nations to promote and motivate women entrepreneurship in developing and under developed countries such as India. India has also supported many ladies entrepreneurs by providing loans and advances, helping them to determine their business, making them self- sufficient by providing vocational skills, and creating many roles for other women in the respective areas. These opportunities are need-based in India, and lots of factors are driving these forces. this text studies these aspects in four parts; the first part deals with growth of women entrepreneurs in south India, the second part studies tapping this growth in financing women entrepreneurs which may be a major problem of failure in their businesses third deals with the role of self help groups (SHGs) in promoting finances and empowering them through capacity building programmes, and therefore the fourth part deals with future policies of the government providing conducive environment for their business.